Rapid and visual detection of Pyricularia oryzae using coupled recombinase polymerase amplification-lateral flow dipstick assay - Du, Yan (Plant disease, 2024)
Rice blast, caused by Pyricularia oryzae, is one of the most destructive fungal diseases in rice, severely impacting rice production worldwide every year. Rapid, accurate and visual detection of P. oryzae is essential for more effective prevention and control. In this study, we developed a recombinase polymerase amplification-lateral flow dipstick (RPA-LFD) assay to detect P. oryzae. Species-specific RPA primer pairs and probe were designed based on target gene MGG_15975. The optimized reaction temperature and time were set at 37 °C and 25 min, respectively. Specificity analysis showed that the assay could specifically detect P. oryzae isolates from rice, whereas other fungal species or Pyricularia species from grasses were not detected. Additionally, this assay demonstrated highly sensitivity, capable of detecting as low as 10-2 ng/µL of P. oryzae genomic DNA, which was found to be 100 times more sensitive than conventional PCR. Furthermore, using this assay, P. oryzae was effectively detected in diseased leaves in rice fields, and could also be identified at an early stage of infection before obvious lesions appeared in artificially inoculated rice seedlings. Therefore, the RPA-LFD assay developed in our study for the detection of P. oryzae is rapid, highly sensitive and efficient, which has the potential application for early diagnosis of P. oryzae infection in rice fields